RESPON TERMOREGULASI SAPI PERAH PADA ENERGI RANSUM YANG BERBEDA (Thermoregulation Response of Dairy Cows on Different Energy Content) - A. Amir; Bagus P. Purwanto; Idat G. Permana (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
The problems faced in dairy cows, among others, is the temperature adaptability in a tropical climate. Low thermal resistance will affect their productivity. This study was conducted to investigate the effect of ration energy on thermoregulatory responses in dairy cows. This research was carried out according to the Latin square design 4 x 4, with 4 treatments ration composition. The variables observed were thermoregulatory responses (body temperature, heart rate, respiration rate), total digestible nutrient (TDN) and body weight gain of dairy cows. The data were statistically analyzed to obtain the mean, standard deviation, variance, descriptions and simple regression analysis. There was a real effect due to treatment ratio energy to body temperature, heart rate, and respiration rate. Ration energy consumption in this study led to the increase of thermoregulatory response from low to high TDN. Therewas a linear relationship between body temperature and TDN intake. Based on the regression analysis, TDN intake signifcantly affected (P<0.01) body temperature with a coeffcient of determination (R2 ) of 0.966. It means that 96.6 percent of the variability in body temperature of dairy cows and can be explained by the independent variables being used in the regression model